Nonaqueous electrolyte secondary battery

By increasing the proportion of silicon-containing material in the negative electrode mixture layer of the nonaqueous electrolyte secondary battery and controlling the volume specific capacity/porosity, combined with the use of sulfonic acid compounds on the positive electrode active material, the problem of large volume changes and poor durability of the negative electrode of the silicon-containing material during charging and discharging is solved, and a balance of high capacity and high durability is achieved.

CN119895607APending Publication Date: 2025-04-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060405.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-26
Filing Date
2023-07-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the volume of the negative electrode containing silicon material changes greatly during the charge and discharge process, resulting in problems with durability (charge and discharge cycle characteristics), making it difficult to take into account both high capacity and high durability.

Method used

The ratio of the silicon-containing material in the negative electrode mixture layer is 50 mass % or more, and the volume specific capacity of the negative electrode mixture layer is divided by the value of porosity of 48.0 mAh/cc·% or less, to improve the cycle characteristics. At the same time, a sulfonic acid compound is present on the surface of lithium-containing transition metal composite oxide particles of the positive electrode active material to reduce reaction resistance and improve charge and discharge efficiency.

Benefits of technology

In a high-capacity nonaqueous electrolyte secondary battery, the cycle characteristics are significantly improved, the migration path of cations in the negative electrode is ensured, and the unevenness of the battery reaction is suppressed, thereby improving the durability of the battery and the initial charging and discharge efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895607A_ABST
    Figure CN119895607A_ABST
Patent Text Reader

Abstract

In a nonaqueous electrolyte secondary battery (10) as an example of an embodiment, a positive electrode (11) contains a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the particle surface of the composite oxide, and the sulfonic acid compound is a compound represented by formula (I). In the negative electrode (12), the proportion of the silicon-containing material in the negative electrode active material is 50 mass% or more, and the value obtained by dividing the volume specific capacity of the negative electrode mixture layer (41) by the porosity is 48.0 mAh / cc% or less. In the formula, A is a group 1 or group 2 element, R is a hydrocarbon group, and n is 1 or 2. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art

[0002] Silicon-containing materials have attracted much attention as high-capacity negative electrode active materials. Patent Document 1 discloses a silicon-containing material that contains porous carbon and silicon and can be used for a negative electrode for a secondary battery. The material has 15% by mass or more and 85% by mass or less of silicon, 0.05 cm 3 / g or more and 0.5cm 3 / g or less nitrogen cannot enter the volume, and 1.5g / cm 3 Above and 2.2g / cm 3 The particle skeleton density is as follows. In Patent Document 1, a high-capacity, high-durability, and high-power battery is realized by optimizing the true density and pore state of the silicon-containing material.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application No. 2018-534720 Summary of the invention

[0006] The negative electrode using silicon-containing materials is effective for increasing the capacity of the battery, but the durability (charge and discharge cycle characteristics) of the silicon-containing materials is problematic due to the large volume change during charge and discharge. Therefore, in the prior art including Patent Document 1, a larger amount of graphite than the silicon-containing material is usually used as the negative electrode active material, and it is not easy to achieve both high capacity and high durability.

[0007] The nonaqueous electrolyte secondary battery disclosed herein is a nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a nonaqueous electrolyte. The positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of particles of the composite oxide. The sulfonic acid compound is a compound represented by formula (I).

[0008]

[0009] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, n is 1 or 2, the negative electrode has a negative electrode mixture layer containing a silicon-containing material as a negative electrode active material, the proportion of the silicon-containing material in the negative electrode active material is more than 50% by mass, and the value obtained by dividing the volume specific capacity of the negative electrode mixture layer by the porosity is less than 48.0 mAh / cc·%.

[0010] According to the secondary battery negative electrode of the present disclosure, the cycle characteristics can be improved in a high-capacity nonaqueous electrolyte secondary battery including a silicon-containing material. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment. DETAILED DESCRIPTION

[0012] The inventors of the present invention have conducted in-depth research in order to improve the cycle characteristics of high-capacity non-aqueous electrolyte secondary batteries containing a large amount of silicon-containing materials. As a result, it was found that the relationship between the volumetric capacity and porosity of the negative electrode mixture layer containing silicon-containing materials is important for improving the cycle characteristics. Negative electrodes in which the proportion of silicon-containing materials in the negative electrode active material is more than 50% by mass usually have a large capacity reduction accompanying charge and discharge, but it was found that by controlling the value obtained by dividing the volumetric capacity of the negative electrode mixture layer by the porosity (volume specific capacity / porosity) to less than 48.0mAh / cc·%, the above-mentioned capacity reduction can be highly suppressed. The porosity in the present disclosure refers to the proportion of the pores between the negative electrode active material particles in the mixture layer, and the pores within the active material particles are not included in the porosity.

[0013] From the perspective of cycle characteristics, batteries using negative electrodes containing a large amount of silicon-containing materials are difficult to use as batteries for, for example, vehicle-mounted applications, power storage applications, etc., but if pores far exceeding the scope of the prior art are introduced into the negative electrode mixture layer and the volumetric capacity / porosity is controlled to be below 48.0 mAh / cc·%, high capacity and high durability can be highly taken into account. That is, in a non-aqueous electrolyte secondary battery containing a large amount of silicon-containing materials in a manner such that the proportion of silicon-containing materials in the negative electrode active material is 50% by mass or more, the cycle characteristics are specifically improved with a volumetric capacity / porosity of 48.0 mAh / cc·%. When the volumetric capacity / porosity of the negative electrode mixture layer is below 48.0 mAh / cc·%, the migration path of the cations in the negative electrode can be fully ensured, and the inhomogeneity of the battery reaction can be suppressed, and it is believed that the cycle characteristics are greatly improved.

[0014] Furthermore, it was confirmed that: by the presence of the sulfonic acid compound shown in the above formula (I) on the surface of the particles of the lithium-containing transition metal composite oxide used as the positive electrode active material, a non-aqueous electrolyte secondary battery with higher capacity and excellent initial charge and discharge efficiency can be achieved. It is believed that the reason is that the reaction resistance in the positive electrode is reduced by the function of the sulfonic acid compound, and the charge and discharge depth can be deepened. On the other hand, if the charge and discharge depth becomes deeper due to the reduction in reaction resistance, there is a concern that the cycle characteristics will be reduced. By using a lithium-containing transition metal composite oxide with a specific sulfonic acid compound attached to the surface of the particles as the positive electrode active material and making the volume specific capacity / porosity of the negative electrode mixture layer less than 48.0mAh / cc·%, it is possible to ensure high capacity while improving the initial charge and discharge efficiency and cycle characteristics.

[0015] Hereinafter, an example of an embodiment of the nonaqueous electrolyte secondary battery of the present disclosure will be described in detail with reference to the drawings. It should be noted that a configuration obtained by selectively combining the various configuration features of the multiple embodiments and modifications described below is included in the scope of the present disclosure.

[0016] Hereinafter, as a non-aqueous electrolyte secondary battery, a cylindrical battery in which a wound electrode body 14 is housed in an outer can 16 having a bottomed cylindrical shape is exemplified, but the outer shell of the battery is not limited to a cylindrical outer can. The non-aqueous electrolyte secondary battery disclosed herein may be, for example, a square battery having a square outer can, a coin-shaped battery having a coin-shaped outer can, or a bag-shaped battery having an outer shell composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.

[0017] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for convenience of description, the sealing body 17 side of the battery is set as the upper side, and the bottom side of the outer can 16 is set as the lower side.

[0018] The non-aqueous electrolyte has lithium ion conductivity and may be a liquid electrolyte (electrolyte) or a solid electrolyte.

[0019] Liquid electrolyte (electrolyte) comprises non-aqueous solvent and electrolyte salt dissolved in non-aqueous solvent. Non-aqueous solvent can use ester, ether, nitrile, amide and these two kinds of mixed solvent etc. for example. As an example of non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and their mixed solvent etc. can be cited. Non-aqueous solvent can also contain halogen substitution (for example, fluoroethylene carbonate etc.) formed by at least a part of hydrogen of these solvents being replaced by halogen atoms such as fluorine. Electrolyte salt uses lithium salt such as LiPF6 for example.

[0020] As a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, a well-known material in a fully solid lithium-ion secondary battery, etc. (for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a halogen-based solid electrolyte, etc.) can be used. The polymer electrolyte, for example, comprises a lithium salt and a matrix polymer, or comprises a non-aqueous solvent, a lithium salt and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent for gelation is used. As polymer materials, fluororesins, acrylic resins, polyether resins, etc. can be listed.

[0021] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0022] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.

[0023] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer can 16, in which a part of the side portion protrudes inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove portion 22 and the open end of the outer can 16 fastened to the sealing body 17.

[0024] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.

[0025] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , in particular, the positive electrode active material constituting the positive electrode 11 and the negative electrode active material constituting the negative electrode 12 will be described in detail.

[0026] [positive electrode]

[0027] The positive electrode 11 has a positive electrode core 30 and a positive electrode mixture layer 31 disposed on the positive electrode core 30. The positive electrode core 30 can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, or the like. The positive electrode mixture layer 31 contains a positive electrode active material, a conductive agent, and a binder, and is preferably disposed on both sides of the positive electrode core 30 except for the portion connected to the positive electrode lead 20. The positive electrode 11 can be manufactured, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder to the surface of the positive electrode core 30, drying the coating, and then compressing to form the positive electrode mixture layer 31 on both sides of the positive electrode core 30.

[0028] As the conductive agent contained in the positive electrode mixture layer 31, carbon black such as acetylene black and ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials can be exemplified. As the binder contained in the positive electrode mixture layer 31, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can also be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide, etc. The content of the conductive agent and the binder relative to the mass of the negative electrode mixture layer 31 is, for example, 0.1% by mass or more and 5% by mass or less.

[0029] The positive electrode 11 includes a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The lithium-containing transition metal composite oxide with the sulfonic acid compound attached to the particle surface functions as a positive electrode active material. The sulfonic acid compound is a compound represented by formula (I).

[0030]

[0031] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.

[0032] The sulfonic acid compound represented by formula (I) (hereinafter, sometimes referred to as "sulfonic acid compound"), when applied to the surface of particles of lithium-containing transition metal oxide, specifically functions to reduce the reaction resistance in the positive electrode 11. As a result, the depth of charge and discharge can be deepened, and further high capacity can be achieved. The sulfonic acid compound can exert this effect even in a very small amount, but it is preferably present on the particle surface of the composite oxide in an amount of 0.01% by mass or more relative to the lithium-containing transition metal composite oxide. The content of the sulfonic acid compound is more preferably 0.05% by mass or more, and particularly preferably 0.10% by mass or more relative to the lithium-containing transition metal composite oxide.

[0033] The upper limit of the content of the sulfonic acid compound is not particularly limited, but from the viewpoint of taking both output characteristics and cycle characteristics into consideration, it is preferably 2.0% by mass, more preferably 1.5% by mass, and particularly preferably 1.0% by mass relative to the lithium-containing transition metal composite oxide. The sulfonic acid compound is present, for example, in an amount of 0.05% by mass or more and 1.50% by mass or less, or 0.1% by mass or more and 1.0% by mass or less relative to the lithium-containing transition metal composite oxide.

[0034] The positive electrode active material may be a composite particle containing a lithium transition metal composite oxide with a sulfonic acid compound attached to the particle surface as a main component, and may be substantially composed of only the composite particle. It should be noted that, within the scope of not impairing the purpose of the present disclosure, the positive electrode active material may also contain a composite oxide or other compound other than the composite particle. For example, as part of the positive electrode active material, a composite oxide without a sulfonic acid compound attached to the particle surface may also be included.

[0035] The lithium-containing transition metal oxide preferably has a layered rock salt structure. When the sulfonic acid compound is applied to a composite oxide with a layered rock salt structure, the above effect becomes more significant. As the layered rock salt structure of the lithium-containing transition metal oxide, for example, a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. can be listed. Among them, from the viewpoint of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred. The layered rock salt structure of the lithium-containing transition metal oxide comprises a transition metal layer, a Li layer and an oxygen layer.

[0036] The lithium-containing transition metal oxide is a composite oxide containing metal elements such as Co, Mn, Ni, and Al in addition to Li. The metal element constituting the lithium-containing transition metal oxide is, for example, at least one selected from Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, and Bi. Among them, it is preferred to contain at least one selected from Co, Ni, and Mn. As an example of a suitable composite oxide, a composite oxide containing Ni, Co, and Mn and a composite oxide containing Ni, Co, and Al can be listed.

[0037] From the viewpoint of high capacity, the lithium-containing transition metal oxide preferably contains more than 50 mol%, more preferably more than 70 mol%, and particularly preferably more than 80 mol% of Ni relative to the total molar number of metal elements other than Li. In addition, the effect of adding the sulfonic acid compound is more significant when a lithium-containing transition metal oxide with a high Ni content is used. The Ni content can be more than 85 mol% or more than 90 mol% relative to the total molar number of metal elements other than Li. The upper limit of the Ni content is, for example, 95 mol%.

[0038] As described above, an example of a suitable lithium-containing transition metal oxide is a composite oxide containing Ni, Co, and Al. Relative to the total molar number of metal elements other than Li, the content of Al is 4 mol% or more and 15 mol% or less, and the content of Co is 1.5 mol% or less. If the content of Al is within this range, it contributes to the stabilization of the crystal structure and the improvement of the cycle characteristics. Co may also be substantially not added, and the battery performance is improved by adding a small amount of Co.

[0039] Lithium-containing transition metal oxides are, for example, a Ni x Al y Co z M1 w O 2-b (wherein, 0.8≤a≤1.2, 0.50≤x≤0.95, 0.04≤y≤0.15, 0≤z≤0.015, 0≤w≤0.50, 0≤b<0.05, x+y+z+w=1, M1 is at least one element selected from the group consisting of Mn, Fe, Ti, Si, Nb, Zr, Mo and Zn). M1 is preferably Mn.

[0040] The content of elements constituting the lithium-containing transition metal composite oxide can be measured by using an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.

[0041] The lithium-containing transition metal composite oxide is, for example, a secondary particle formed by the aggregation of multiple primary particles. The volume-based median particle size (D50) of the composite oxide is not particularly limited, and as an example, is 3 μm or more and 30 μm or less, preferably 5 μm or more and 25 μm or less. In the case where the composite oxide is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size at which the cumulative frequency from the smaller particle size in the volume-based particle size distribution becomes 50%, also known as the median diameter. The particle size distribution of the composite oxide (the same is true for the negative electrode active material) is measured using a laser diffraction particle size distribution measuring device (for example, Microtrac Bell Co., Ltd., MT3000II) and water as the dispersion medium.

[0042] The average particle size of the primary particles constituting the lithium-containing transition metal composite oxide is, for example, 0.05 μm to 1 μm. The average particle size of the primary particles is calculated by averaging the diameters of the circumscribed circles of the primary particles extracted by analyzing a scanning electron microscope (SEM) image of a cross section of the secondary particles.

[0043] As described above, the sulfonic acid compound present on the surface of the particles of the lithium-containing transition metal composite oxide is a compound represented by formula (I).

[0044]

[0045] In the formula, A is an element of Group 1 or Group 2, R is a hydrocarbon group, and n is 1 or 2. A is preferably an element of Group 1. Among them, Li or Na is more preferred, and Li is particularly preferred.

[0046] In formula (I), R is preferably an alkyl group. The carbon number of the alkyl group is preferably 5 or less, more preferably 3 or less. From the viewpoint of reducing the reaction resistance, an example of a suitable R is an alkyl group having a carbon number of 3 or less, wherein a methyl group is preferred. It should be noted that, in R, a portion of the hydrogen bonded to the carbon may also be substituted by fluorine. In addition, n in formula (I) is preferably 1.

[0047] Specific examples of the sulfonic acid compound include lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, sodium methanesulfonate, sodium ethanesulfonate, magnesium methanesulfonate, lithium fluoromethanesulfonate, etc. Among them, at least one selected from the group consisting of lithium methanesulfonate, lithium ethanesulfonate and sodium methanesulfonate is preferred, and lithium methanesulfonate is particularly preferred.

[0048] The sulfonic acid compound is, for example, uniformly present on the entire surface of the particles of the lithium-containing transition metal composite oxide. The presence of the sulfonic acid compound on the surface of the composite oxide particles can be confirmed by Fourier transform infrared spectroscopy (FT-IR). In the infrared absorption spectrum obtained by FT-IR, the positive electrode active material containing lithium methanesulfonate, for example, has a peak at 1238 cm -1 、1175cm -1 、1065cm -1 、785cm -1 There is an absorption peak near 1238cm -1 、1175cm -1 、1065cm -1 The peaks near 785cm are caused by the SO stretching vibration of lithium methanesulfonate. -1 The nearby peaks are peaks derived from CS stretching vibration of lithium methanesulfonate.

[0049] For positive electrode active materials containing sulfonic acid compounds other than lithium methanesulfonate, the presence can also be confirmed by the absorption peak derived from the sulfonic acid compound in the infrared absorption spectrum. It should be noted that the presence of the sulfonic acid compound on the particle surface of the lithium-containing transition metal composite oxide can also be confirmed by ICP, atomic absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), radioactive light XRD measurement, TOF-SIMS, etc.

[0050] The positive electrode active material as an example of the embodiment can be produced by the following method. It should be noted that the production method described here is an example, and the production method of the positive electrode active material is not limited to this method.

[0051] First, a metal oxide containing metal elements such as Ni, Al, Co, and Mn is synthesized. Then, the metal oxide and a lithium compound are mixed and calcined to obtain a lithium-containing transition metal composite oxide. The metal oxide is synthesized, for example, by stirring a solution of a metal salt containing Ni, Al, Co, Mn, etc., while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to the alkaline side (for example, 8.5 or more and 12.5 or less), so that a composite hydroxide containing metal elements such as Ni, Al, Co, and Mn is precipitated (coprecipitated), and the composite hydroxide is heat-treated to synthesize a metal oxide. The heat treatment temperature is not particularly limited, and as an example, it is 300° C. or more and 600° C. or less.

[0052] Examples of lithium compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. The metal oxide and the lithium compound are mixed, for example, in a manner such that the molar ratio of the metal element in the metal oxide to the Li in the lithium compound is 1:0.98 or more and 1:1.1 or less. It should be noted that when mixing the metal oxide and the lithium compound, other metal raw materials may be added as needed.

[0053] The mixture of the metal oxide and the lithium compound is calcined, for example, in an oxygen atmosphere. The mixture may also be calcined through multiple temperature rising processes. The calcining process includes the following steps: a first temperature rising process of heating the temperature to 450°C or higher and 680°C or lower at a temperature rising rate of, for example, 1.0°C / min or higher and 5.5°C / min or lower; and a second temperature rising process of heating the temperature to a temperature exceeding 680°C at a temperature rising rate of 0.1°C / min or higher and 3.5°C / min or lower. The maximum reaching temperature of the calcining process may be set to 700°C or higher and 850°C or lower, and the temperature may be maintained for 1 hour or higher and 10 hours or lower.

[0054] Next, the calcined product (lithium-containing transition metal composite oxide) is washed with water and dehydrated to obtain a cake-like composition. The residual alkali component is removed by this washing process. The washing and dehydration can be carried out using existing known methods. Next, the cake-like composition is dried to obtain a powdery composition. The drying process can also be carried out under a vacuum atmosphere. An example of drying conditions is at a temperature of 150° C. or more and 400° C. or less for 0.5 hours or more and 15 hours or less.

[0055] The sulfonic acid compound is added to the cake-like composition obtained in the washing step, for example, or to the powder-like composition obtained in the drying step. At this time, a sulfonic acid solution may be added instead of the sulfonic acid compound or together with the sulfonic acid compound. Thus, a positive electrode active material having a sulfonic acid compound attached to the surface of particles of the lithium-containing transition metal composite oxide can be obtained. The sulfonic acid compound may be added as an aqueous dispersion. In addition, the sulfonic acid solution is preferably an aqueous solution of sulfonic acid. The concentration of sulfonic acid in the sulfonic acid solution is, for example, 0.5% by mass or more and 40% by mass or less.

[0056] Note that, since a certain amount of lithium compound remains in the cake-like composition, by adding the sulfonic acid solution to the cake-like composition, Li dissolved in water in the cake reacts with the sulfonic acid to obtain lithium sulfonate.

[0057] [negative electrode]

[0058] The negative electrode 12 includes a negative electrode core 40 and a negative electrode mixture layer 41 disposed on the negative electrode core 40. The negative electrode core 40 may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode mixture layer 41 includes a negative electrode active material and a binder, and is preferably disposed on both sides of the negative electrode core 40 except for a portion connected to the negative electrode lead 21. The negative electrode 12 can be manufactured, for example, by applying a negative electrode mixture slurry including a negative electrode active material and a binder to the surface of the negative electrode core 40, drying the coating, and then compressing the coating to form the negative electrode mixture layer 41 on both sides of the negative electrode core 40.

[0059] Among the binders contained in the negative electrode mixture layer 41, fluororesins, PAN, polyimides, acrylic resins, polyolefins, etc. can also be used as in the case of the positive electrode 11, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode mixture layer 41 preferably contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, it is suitable to use SBR in combination with CMC or its salt, PAA or its salt. The content of the binder is, for example, 0.1% by mass or more and 5% by mass or less relative to the mass of the negative electrode mixture layer 41. It should be noted that the negative electrode mixture layer 41 may also contain conductive agents such as CNT.

[0060] The negative electrode mixture layer 41 contains a silicon-containing material as a negative electrode active material. The proportion of the silicon-containing material in the negative electrode active material is more than 50% by mass. Compared with carbon-based active materials such as graphite that are usually used as negative electrode active materials, the silicon-containing material can absorb more Li ions. Therefore, by increasing the content of the silicon-containing material, the battery can be increased in capacity. The details will be described later. When the content of the silicon-containing material is simply increased, the cycle characteristics are greatly reduced. Therefore, in order to take into account both high capacity and high durability in the non-aqueous electrolyte secondary battery 10, the value obtained by dividing the volumetric capacity of the negative electrode mixture layer 41 by the porosity (hereinafter referred to as "volume specific capacity / porosity") is set to less than 48.0mAh / cc·%.

[0061] The proportion (content) of the silicon-containing material in the negative electrode active material is preferably 60% by mass or more, more preferably 70% by mass or more, particularly preferably 80% by mass or more, and may be 90% by mass or more. The upper limit of the content of the silicon-containing material is not particularly limited and may be 100% by mass. An example of a suitable range of the content of the silicon-containing material is 70 to 100% by mass of the mass of the negative electrode active material, more preferably 80% by mass or more and 100% by mass or less. In the negative electrode mixture layer 41, as the negative electrode active material, it may substantially only contain silicon-containing materials, but it may also contain carbon materials in an amount of 50% by mass or less.

[0062] The carbon material that functions as the negative electrode active material is, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon and hard carbon. Among them, as the carbon material, it is preferred to use at least artificial graphite such as blocky artificial graphite (MAG), graphitized mesophase carbon microbeads (MCMB), natural graphite such as flaky graphite, blocky graphite, and earthy graphite, or a mixture thereof. The volume-based D50 of the carbon material is, for example, 1 μm or more and 30 μm or less, preferably 5 μm or more and 25 μm or less.

[0063] Soft carbon and hard carbon are classified as amorphous carbon with an underdeveloped graphite crystal structure. More specifically, it refers to a carbon component with a d(002) interplanar spacing of 0.342 nm or more based on X-ray diffraction. Soft carbon is also called graphitizable carbon, which is carbon that is easily graphitized by high-temperature treatment compared to hard carbon. Hard carbon is also called difficult-to-graphitize carbon. It should be noted that in the composition of the present invention, there is no need to clearly distinguish between soft carbon and hard carbon. As a negative electrode active material, graphite and at least one amorphous carbon of soft carbon and hard carbon can also be used in combination.

[0064] As described above, the volumetric capacity / porosity of the negative electrode mixture layer 41 is 48.0 mAh / cc·% or less. It is believed that the pores between the particles of the negative electrode active material become the main migration path of the Li ions that migrate in the negative electrode mixture layer 41 accompanying charging and discharging. It is believed that if the value of the volumetric capacity / porosity of the negative electrode mixture layer 41 is 48.0 mAh / cc·% or less, the migration path of the Li ions can be fully ensured. In addition, it is believed that if it is 48.0 mAh / cc·% or less, the effect of the expansion of the silicon-containing material during charging can be fully alleviated. If the volumetric capacity / porosity is 48.0 mAh / cc·% or less, based on this reason, the capacity reduction accompanying charging and discharging can be highly suppressed, and the cycle characteristics can be greatly improved.

[0065] The cycle characteristics of the non-aqueous electrolyte secondary battery 10 vary greatly when the volumetric capacity / porosity of the negative electrode mixture layer 41 reaches 48.0 mAh / cc·%, so, for example, from the perspective of the stability of battery performance, the volumetric capacity / porosity is controlled to be below 45.0 mAh / cc·%. An example of a suitable volumetric capacity / porosity is below 45.0 mAh / cc·%, or below 40.0 mAh / cc·%.

[0066] The lower limit of the volumetric capacity / porosity of the negative electrode mixture layer 41 is not particularly limited. Even if it is too small, the improvement effect of the cycle characteristics reaches a peak, so it is preferably 25.0 mAh / cc·%, and more preferably 30.0 mAh / cc·%. When the volumetric capacity / porosity of the negative electrode mixture layer 41 is 48.0 mAh / cc·% or less and 25.0 mAh / cc·% or more, or 30.0 Ah / cc·% or more, it is possible to further achieve a high balance between high capacity and high durability.

[0067] In the present disclosure, the volumetric specific capacity of the negative electrode mixture layer is measured by the following method.

[0068] (1) The battery to be evaluated was disassembled and the negative electrode plate was cut out. A monopolar battery cell was prepared using metal Li as the counter electrode and an ionic liquid as the electrolyte.

[0069] (2) The monopolar battery cell was charged at 0.1 C until the battery cell voltage reached 5 mV under a temperature environment of 25° C., and after a 20-minute pause, it was discharged at 0.1 C until the battery cell voltage reached 1.0 V to determine the discharge capacity (C).

[0070] (3) The discharge capacity (C) was divided by the volume (Va) of the negative electrode mixture layer in the discharged state to calculate the volume specific capacity (Cv (mAh / cc) = C / Va).

[0071] The porosity of the negative electrode mixture layer 41 is preferably greater than 25%, more preferably greater than 35%, or greater than 40%. As described above, the porosity refers to the proportion of the pores between the negative electrode active material particles in the negative electrode mixture layer 41, and the pores within the active material particles are not included in the porosity. The porosity of the negative electrode mixture layer 41 is controlled in such a way that the volumetric capacity / porosity becomes a target value, for example, it changes according to the compression conditions of the negative electrode mixture layer 41 when manufacturing the negative electrode 12. Generally, if the compression force of the negative electrode mixture layer 41 is reduced, the porosity becomes higher, and if the compression force is increased, the porosity becomes lower. The porosity of the negative electrode mixture layer 41 can also be controlled by the particle size distribution of the negative electrode active material, etc.

[0072] The upper limit of the porosity of the negative electrode mixture layer 41 is not particularly limited, but even if the porosity is too high, the improvement effect of the cycle characteristics reaches a peak, so it is preferably 65%, and more preferably 60% or 55%. When the porosity of the negative electrode mixture layer 41 is 25% or more and 65% or less, or 60% or less, it is possible to further achieve both high capacity and high durability.

[0073] In the present disclosure, the porosity of the negative electrode mixture layer is measured using a mercury porosimeter.

[0074] (1) After the battery to be evaluated is discharged to 2.5 V, the battery is disassembled, the negative electrode plates are cut out, and a plurality of negative electrode plates as samples are placed in a measurement cell of a mercury porosimeter.

[0075] (2) In order to prevent the gaps between the samples from being counted as pores, the total volume (Vh) of mercury pressed into pores with a pore diameter of 20 μm or more was determined.

[0076] (3) The total volume of mercury (Vh) is divided by the volume of the negative electrode mixture layer in the discharged state (Va) to calculate the porosity (P (%) = Vh × 100 / Va).

[0077] The density of the negative electrode mixture layer 41 is preferably 1.5 g / cc or less, and more preferably 1.2 g / cc or less. In this case, the improvement effect of the cycle characteristics becomes more significant. From the perspective of both high capacity and high durability, the lower limit of the density is preferably 0.65 g / cc. An example of a suitable range of the density of the negative electrode mixture layer 41 is 0.65 g / cc or more and 1.5 g / cc or more and 1.2 g / cc or less. The density of the negative electrode mixture layer 41 is lower as the porosity is higher when the material used is the same.

[0078] In the present disclosure, the density of the negative electrode mixture layer is measured by the following method.

[0079] (1) After the battery to be evaluated was discharged to 2.5 V, the battery was disassembled, the negative electrode plate was cut out, immersed in DMC for cleaning, and vacuum dried at 100° C. for 5 hours, and then the mass (Wa) of the negative electrode plate was measured.

[0080] (2) The negative electrode mixture layer was peeled off from the negative electrode plate, and ultrasonic cleaning was performed, and then the mass (Wc) of the negative electrode core was measured.

[0081] (3) The mass of the negative electrode mixture layer is obtained by subtracting the mass of the negative electrode core (Wc) from the mass of the negative electrode plate (Wa). The mass of the negative electrode mixture layer is divided by the volume of the negative electrode mixture layer in the discharged state (Va) to calculate the density of the negative electrode mixture layer (D (g / cc) = (Wa-Wc) / Va).

[0082] The particle expansion rate of the silicon-containing material is preferably 3.0 times or less. From the viewpoint of improving the cycle characteristics, the particle expansion rate of the silicon-containing material is preferably 3.0 times or less, but if the particle expansion rate is too small, it is seen that the capacity tends to decrease. Therefore, the particle expansion rate of the silicon-containing material is preferably 1.1 times or more. An example of a suitable range of the particle expansion rate is 1.1 times or more and 3.0 times or less, more preferably 1.3 times or more and 2.1 times or less. If the particle expansion rate of the silicon-containing material is within this range, it becomes easy to take into account both high capacity and high durability.

[0083] In this specification, the particle expansion rate of the silicon-containing material is measured by the following method.

[0084] (1) The battery to be evaluated was disassembled, the negative electrode plate was cut out, metal Li was used as the counter electrode, and an ionic liquid was used as the electrolyte to prepare a monopolar battery cell in which the cross section of the silicon-containing material particles was exposed.

[0085] (2) The monopolar battery cell was charged at 0.002C at a temperature of 25°C until the battery cell voltage reached 0.6V. After a 10-minute pause, the battery cell was discharged at 0.05C until the battery cell voltage reached 1.9V. The cross-section of the silicon-containing material particles was observed in situ using a SEM.

[0086] (3) Based on the change in the cross-sectional area of ​​the silicon-containing material particles, the cross-sectional area of ​​the silicon-containing material particles in the charged state (Spc) and the cross-sectional area of ​​the silicon-containing material particles in the discharged state (Spd) are obtained, and the particle expansion rate is calculated (Sp = (Spc / Spd)1.5).

[0087] The expansion rate of the negative electrode mixture layer 41 depends on the expansion rate and the addition amount of the negative electrode active material. The expansion rate of the negative electrode mixture layer 41 is preferably 1.5 times or less. In this case, the improvement effect of the cycle characteristics becomes more significant. The lower limit of the expansion rate of the negative electrode mixture layer 41 is not particularly limited, and as an example, it is 1.1 times. An example of a suitable range of the expansion rate of the negative electrode mixture layer 41 is greater than 1.1 times and less than 1.5 times, and more preferably greater than 1.2 times and less than 1.4 times. If the expansion rate of the negative electrode mixture layer 41 is within this range, it becomes easy to take into account both high capacity and high durability.

[0088] In the present disclosure, the expansion rate of the negative electrode mixture layer is measured by the following method.

[0089] (1) The battery to be evaluated was disassembled, the negative electrode plate was cut out, and a monopolar battery cell was prepared using metal Li as the counter electrode and an ionic liquid as the electrolyte.

[0090] (2) The monopolar battery cell was charged at 0.1C until the battery cell voltage reached 5 mV in a temperature environment of 25°C, and after a 20-minute pause, it was discharged at 0.1C until the battery cell voltage reached 1.0V.

[0091] (3) The thickness of the negative electrode mixture layer in a charged state (Tac) and the thickness of the negative electrode mixture layer in a discharged state (Tad) are obtained, and the expansion rate of the negative electrode mixture layer is calculated as the ratio of the thicknesses (Sa=Tac / Tad).

[0092] The silicon-containing material is a material containing Si, and as an example, silicon alloys, silicon compounds and composite materials containing Si can be listed. Among them, composite materials containing Si are preferred. The D50 of the silicon-containing material is usually smaller than the D50 of graphite. The volume-based D50 of the silicon-containing material is, for example, greater than 1 μm and less than 20 μm, or greater than 1 μm and less than 15 μm. It should be noted that the silicon-containing material can be used alone or in combination of two or more.

[0093] Suitable silicon-containing materials (composite materials) are composite particles comprising an ion-conducting phase and a Si phase dispersed in the ion-conducting phase. The ion-conducting phase is, for example, at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase. The silicide phase is a phase of a compound composed of Si and an element that is more electrically positive than Si, and as an example, NiSi, Mg2Si, TiSi2, etc. can be cited. The Si phase is formed by dispersing Si into fine particles. The ion-conducting phase is a continuous phase composed of a collection of particles that are finer than the Si phase.

[0094] The average value of the size (crystallite size) of the Si phase is preferably greater than 1 nm and less than 200 nm, more preferably greater than 1 nm and less than 100 nm. For the average value of the size of the Si phase, the formula D = kλ / Bcosθ (k = 0.89, λ = 0.15418, 2θ = 28.4°, B is the half-value full width) is used to calculate the half-value width of the peak (2θ = 28.4°) derived from Si in the XRD spectrum. The average size of the Si phase can be, for example, greater than 1 nm and less than 10 nm. By reducing the size of the Si phase, it is possible to maintain a high capacity and suppress the particle expansion rate associated with charging and discharging.

[0095] The composite material may also have a conductive layer covering the surface of the ion conductive phase. The conductive layer is composed of a material with higher conductivity than the ion conductive layer, and forms a good conductive path in the negative electrode mixture layer 41. The conductive layer is, for example, a carbon coating composed of a conductive carbon material. The conductive carbon material may use carbon black such as acetylene black and ketjen black, graphite, amorphous carbon (amorphous carbon) with low crystallinity, etc. Considering the conductivity and the diffusibility of Li ions to the interior of the particles, the thickness of the conductive layer is preferably 1 nm or more and 200 nm or less, or 5 nm or more and 100 nm or less. The thickness of the conductive layer can be measured by cross-sectional observation of the composite material using an SEM or a transmission electron microscope (TEM).

[0096] The ionic conduction phase may also contain at least one selected from the group consisting of Group 1 and Group 2 elements of the periodic table. The ion conductive layer may also be a silicon oxide phase doped with Li. Additionally, the ionic conduction phase may also contain at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F, W, and lanthanide elements.

[0097] An example of a suitable composite material containing Si is a composite particle having an island structure in which fine Si is substantially uniformly dispersed in an amorphous silicon oxide phase and having a general formula SiO x (0 < x ≤ 2). The main component of the silicon oxide may also be silicon dioxide. Additionally, the silicon oxide phase may also be doped with Li. The content ratio (x) of oxygen to Si is, for example, 0.5 ≤ x < 2.0, preferably 0.8 ≤ x ≤ 1.5.

[0098] Another example of a suitable composite material containing Si is a composite particle having an island structure in which fine Si is substantially uniformly dispersed in an amorphous silicate phase. A suitable silicate phase is a lithium silicate phase containing Li. The lithium silicate phase is, for example, a phase of a composite oxide represented by the general formula Li 2z SiO (2+z) (0 < z < 2). It is preferred that the lithium silicate phase does not contain Li4SiO4 (Z = 2). Li4SiO4 is an unstable compound and reacts with water to show alkalinity, and thus sometimes deteriorates Si, resulting in a decrease in charge-discharge capacity. From the viewpoints of stability, productivity, Li ion conductivity, etc., the lithium silicate phase preferably has Li2SiO3 (Z = 1) or Li2Si2O5 (Z = 1 / 2) as the main component.

[0099] Another example of a suitable composite material containing Si is a composite particle having an island structure in which fine Si is substantially uniformly dispersed in a carbon phase. The carbon phase is preferably an amorphous carbon phase. The carbon phase may also contain a crystalline phase component, but preferably has a large amount of amorphous phase component. The amorphous carbon phase is composed of a carbon material having an average crystal plane spacing of the (002) plane exceeding 0.34 nm measured by, for example, X-ray diffraction method. It should be noted that the composite material containing a carbon phase may or may not have a conductive layer different from the carbon phase.

[0100] [Separator]

[0101] The separator 13 uses a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, nonwoven fabrics, etc. can be cited. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin can be formed on the surface of the separator 13.

[0102] A filler layer containing an inorganic filler may also be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.

[0103] The nonaqueous electrolyte secondary battery 10 having the above-mentioned structure preferably has a charging upper limit voltage of 4.2V and a cutoff voltage of 2.0V. That is, the nonaqueous electrolyte secondary battery 10 preferably controls charging and discharging within a voltage range of 2.0V to 4.2V. More preferably, the charging and discharging is controlled within a voltage range of 2.5V to 4.2V. In this case, high capacity and high durability can be further highly balanced.

[0104] Example

[0105] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.

[0106] <Example 1>

[0107] [Synthesis of positive electrode active material]

[0108] The [Ni 0.90 Al 0.05 Mn 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain an oxide (Ni 0.90 Al 0.05 Mn 0.05 Next, LiOH and the composite oxide were mixed so that the molar ratio of Li to the total amount of Ni, Al and Mn was 1.03:1 to obtain a mixture. The mixture was placed under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The mixture was calcined at a rate of 2.0°C / min from room temperature to 650°C, and then calcined at a rate of 0.5°C / min from 650°C to 780°C to obtain a lithium-containing transition metal composite oxide.

[0109] Water is added to the obtained lithium-containing transition metal composite oxide to make the slurry concentration become 1500g / L, stirred for 15 minutes, filtered, and a cake-like composition is obtained. Powdered lithium methanesulfonate is added to the cake-like composition. The amount of lithium methanesulfonate added is 0.1% by mass relative to the total mass of the lithium-containing transition metal composite oxide. After adding lithium methanesulfonate, it is dried under vacuum atmosphere at 180°C for 2 hours to obtain a positive electrode active material. It should be noted that the presence of lithium methanesulfonate on the particle surface of the composite oxide was confirmed by Fourier transform infrared spectroscopy (FT-IR).

[0110] [Production of positive electrode]

[0111] The positive electrode active material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to the positive electrode core formed by aluminum foil, and after the coating is dried and compressed, the positive electrode core is cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a part of the positive electrode.

[0112] [Production of negative electrode]

[0113] As the silicon-containing material, composite particles having a sea-island structure in which fine Si is roughly uniformly dispersed in the carbon phase are used (average value of the size of the Si phase: 5 nm, D50: 10 μm, true density: 1.5 g / cc). Using the silicon-containing material as the negative electrode active material, a dispersion of the negative electrode active material, sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) are mixed at a solid component mass ratio of 100:1:1, and water is used as a dispersion medium to prepare a negative electrode mixture slurry. The negative electrode mixture slurry is applied to both sides of a negative electrode core formed by copper foil, and after the coating film is dried, the coating film is compressed using a roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core. It should be noted that an exposed portion where the surface of the negative electrode core is exposed is provided on a part of the negative electrode.

[0114] [Preparation of non-aqueous electrolyte]

[0115] LiPF6 was dissolved at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (MEC) and dimethyl carbonate (DMC) in a volume ratio of 3:3:4 (25°C) to prepare a non-aqueous electrolyte.

[0116] [Fabrication of test battery cell (non-aqueous electrolyte secondary battery)]

[0117] Leads are installed on the positive electrode and the negative electrode, respectively, and the positive electrode and the negative electrode are wound into a spiral shape through a separator, thereby obtaining a wound electrode body. The electrode body is housed in a bottomed cylindrical outer can, and the negative electrode lead is welded to the inner surface of the bottom of the outer can, and the positive electrode lead is welded to the internal terminal plate of the sealing body. Then, the non-aqueous electrolyte is injected into the outer can, and the opening edge of the outer can is riveted and fixed to the sealing body to produce a cylindrical test battery cell.

[0118] The particle expansion rate of the silicon-containing material, the density of the negative electrode mixture layer and the expansion rate of the negative electrode mixture layer were measured using the above method. The results showed that the particle expansion rate was 1.78 times, the density of the negative electrode mixture layer was 0.864 g / cc, and the expansion rate of the negative electrode mixture layer was 1.27 times.

[0119] The initial charge and discharge efficiency and cycle characteristics (capacity retention rate) of the above-mentioned test battery cells were evaluated by the following method, and the evaluation results are shown in Table 1. The same evaluation was performed on each test battery cell of the following examples and comparative examples, and the evaluation results are shown in Table 1 together with the physical properties of the negative electrode. In Table 1, Examples 1 to 10 are designated as A1 to A10, and Comparative Examples 1 to 6 are designated as B1 to B6. The capacity retention rate of each test battery cell shown in Table 1 is a relative value when the capacity retention rate of the test battery cell of Example 1 (A1) is designated as 100.

[0120] [Evaluation of initial charge and discharge efficiency]

[0121] The test battery cell was charged at a constant current of 0.5C until the battery voltage reached 4.1V under a temperature environment of 25°C, and then charged at a constant voltage of 4.1V until the current value reached 0.05C. Then, the constant current was discharged at a current value of 0.7C until the battery voltage reached 2.85V. The charge capacity and discharge capacity during the charge and discharge were obtained, and the ratio of the discharge capacity to the charge capacity (discharge capacity × 100 / charge capacity) was calculated as the initial charge and discharge efficiency.

[0122] [Evaluation of Cycle Characteristics (Capacity Retention Rate)]

[0123] The above charge and discharge were performed 100 times, the discharge capacity at the first cycle and the discharge capacity at the 100th cycle were determined, and the capacity retention rate was calculated according to the following formula.

[0124] Capacity retention rate (%) = (100th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100

[0125] <Examples 2 to 10>

[0126] A negative electrode and a nonaqueous electrolyte secondary battery were prepared in the same manner as in Example 1 except that the compression conditions of the negative electrode mixture layer were changed so that the volumetric capacity / porosity of the negative electrode mixture layer was set to the values ​​shown in Table 1, and the above-mentioned performance evaluation was performed.

[0127] <Comparative Examples 1 to 6>

[0128] The negative electrode and non-aqueous electrolyte secondary battery were prepared in the same manner as in Example 1 except that the compression conditions of the negative electrode mixture layer were changed and the volume specific capacity / porosity value of the negative electrode mixture layer was set to the value shown in Table 1, and the above-mentioned performance evaluation was performed. It should be noted that in the test battery cells of Comparative Examples 4 to 6, a significant decrease in the capacity retention rate was confirmed at the beginning of the cycle.

[0129] [Table 1]

[0130]

[0131] As shown in Table 1, the test cell of the embodiment has a higher capacity retention rate after the cycle test and is excellent in cycle characteristics than the test cells of Comparative Examples 1 to 6. In addition, the test cell of the embodiment has a higher initial charge and discharge efficiency than the test cells of Comparative Examples 5 and 6. In the present embodiment and comparative examples, when lithium methanesulfonate is used as the positive electrode but no sulfonic acid compound is used, the charge and discharge efficiency is reduced.

[0132] From the evaluation results shown in Table 1, it can be seen that when the volumetric capacity / porosity value of the negative electrode mixture layer is 48.0 mAh / cc·% or less, the capacity retention rate is specifically improved and the cycle characteristics are improved. In other words, if the volumetric capacity / porosity value of the negative electrode mixture layer exceeds 48.0 mAh / cc·%, the cycle characteristics are sharply reduced. In particular, when the volumetric capacity / porosity exceeds 70 mAh / cc·%, the charge and discharge efficiency is also greatly reduced.

[0133] As described above, in a non-aqueous electrolyte secondary battery in which the proportion of silicon-containing materials in the negative electrode active material is 50% by mass or more, by using a sulfonic acid compound in the positive electrode and controlling the volumetric capacity / porosity of the negative electrode mixture layer to below 48.0 mAh / cc·%, it is possible to improve the charge and discharge efficiency and achieve both high capacity and high durability.

[0134] The present disclosure is further described through the following embodiments.

[0135] Configuration 1: A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte,

[0136] The positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles.

[0137] The aforementioned sulfonic acid compound is a compound represented by formula (I),

[0138]

[0139] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, n is 1 or 2,

[0140] The negative electrode has a negative electrode mixture layer containing a silicon-containing material as a negative electrode active material, the proportion of the silicon-containing material in the negative electrode active material is greater than 50 mass%, and the value obtained by dividing the volume specific capacity of the negative electrode mixture layer by the porosity is less than 48.0 mAh / cc·%.

[0141] Configuration 2: The nonaqueous electrolyte secondary battery according to Configuration 1, wherein the sulfonic acid compound is present in an amount of 0.1 mass % or more and 1.0 mass % or less relative to the lithium-containing transition metal composite oxide.

[0142] Configuration 3: The nonaqueous electrolyte secondary battery according to Configuration 1 or Configuration 2, wherein A in formula (I) is Li or Na.

[0143] Configuration 4: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R in formula (I) is an alkyl group having 3 or less carbon atoms.

[0144] Configuration 5: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the density of the negative electrode mixture layer is 1.5 g / cc or less.

[0145] Configuration 6: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the silicon-containing material accounts for 70% by mass or more of the negative electrode active material.

[0146] Configuration 7: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 6, wherein the particle expansion rate of the silicon-containing material is 3.0 times or less.

[0147] Configuration 8: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein the negative electrode mixture layer has an expansion coefficient of 1.5 times or less.

[0148] Configuration 9: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 8, wherein the negative electrode mixture layer contains at least one carbon material selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon as the negative electrode active material.

[0149] Configuration 10: A non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 9, wherein the silicon-containing material comprises an ion conductive phase and a Si phase dispersed in the ion conductive phase, and the ion conductive phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase and a silicon oxide phase.

[0150] Configuration 11: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 10, wherein the volume-based median diameter of the silicon-containing material is 1 μm to 20 μm, and the average size of the Si phase is 1 nm to 200 nm.

[0151] Configuration 12: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 11, wherein charge and discharge are controlled within a voltage range of 2.0 V to 4.2 V.

[0152] Description of Reference Numerals

[0153] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 positive electrode core body, 31 positive electrode mixture layer, 40 negative electrode core body, 41 negative electrode mixture layer.

Claims

1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The sulfonic acid compound is a compound represented by formula (I), In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, n is 1 or 2, The negative electrode has a negative electrode mixture layer containing a silicon-containing material as a negative electrode active material, the proportion of the silicon-containing material in the negative electrode active material is greater than 50 mass %, and the value obtained by dividing the volume specific capacity of the negative electrode mixture layer by the porosity is less than 48.0 mAh / cc·%.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The sulfonic acid compound is present in an amount of 0.1 mass % or more and 1.0 mass % or less relative to the lithium-containing transition metal composite oxide.

3. The nonaqueous electrolyte secondary battery according to claim 1, wherein A in formula (I) is Li or Na.

4. The nonaqueous electrolyte secondary battery according to claim 1, wherein R in the formula (I) is an alkyl group having 3 or less carbon atoms.

5. The nonaqueous electrolyte secondary battery according to claim 1, wherein The density of the negative electrode mixture layer is 1.5 g / cc or less.

6. The nonaqueous electrolyte secondary battery according to claim 1, wherein The silicon-containing material accounts for 70 mass % or more and 100 mass % or less in the negative electrode active material.

7. The nonaqueous electrolyte secondary battery according to claim 1, wherein The particle expansion rate of the silicon-containing material is less than 3.0 times.

8. The nonaqueous electrolyte secondary battery according to claim 1, wherein The expansion rate of the negative electrode mixture layer is 1.5 times or less.

9. The nonaqueous electrolyte secondary battery according to claim 1, wherein The negative electrode mixture layer includes at least one carbon material selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon as the negative electrode active material.

10. The nonaqueous electrolyte secondary battery according to claim 1, wherein The silicon-containing material comprises an ion-conducting phase and a Si phase dispersed in the ion-conducting phase, The ion-conducting phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.

11. The nonaqueous electrolyte secondary battery according to claim 10, wherein The volume-based median particle size of the silicon-containing material is greater than or equal to 1 μm and less than or equal to 20 μm, The average value of the size of the Si phase is greater than or equal to 1 nm and less than or equal to 200 nm. 12 . The nonaqueous electrolyte secondary battery according to claim 1 , wherein charge and discharge are controlled within a voltage range of 2.0 V to 4.2 V.

Citation Information

Patent Citations

  • Novel material having highly durable lithium insertion and method for manufacturing the same

    JP2018534720A